Knowledge transformation through board games for fostering perseverance character at TPQ Baitul Khoir Jetakan - Haq, Akhmad Liana Amrul; Purnanto, Arif Wiyat; Fitriyatinur, Qurnia (Community Empowerment, 2025)
This community service activity aimed to transform Islamic learning materials from books into an educational board game format at Taman Pendidikan Al-Qur'an (TPQ) Baitul Khoir Jetakan, Jogonegoro, Mertoyudan. This initiative was designed to create an effective learning process and to foster a character of perseverance among the students. Board games were chosen as an alternative, interactive, and enjoyable learning medium, expected to increase children's motivation and enthusiasm for learning Islamic teachings. The program's implementation showed positive results: 7 children aged from early childhood education (PAUD) to 2nd grade elementary school, who previously only mastered the Pillars of Islam and some names of angels, now successfully memorized all the Pillars of Faith, Pillars of Islam, names of angels, and 3-5 daily prayers. Meanwhile, 15 children aged 3rd-6th grade elementary school successfully memorized the names of prophets along with their miracles, popular Islamic history, 6-10 daily prayers, and were able to correctly practice ablution (wudhu) and prayer (shalat). This game also significantly encouraged social interaction and cooperation among students, supporting the formation of an Islamic character of "perseverance." It is concluded that the transformation of knowledge through board games at TPQ Baitul Khoir was effective in enhancing basic Islamic knowledge and cultivating a character of perseverance in the students.